Life satisfaction as a causal determinant of the second parity progression - JEE, Sang Hoon (KDI School, 2016)
Finding ways to reverse the low fertility trend across developed countries are becoming a national priority. Although there are many possible angles to view this problem, here the issue of low fertility was taken as a matter of personal choice, especially so for a second child. Based on this premise, it was determined that critical but often neglected determinant of fertility behaviors was the life satisfaction, which is an integral aspect of human life that can not only reflect a person’s living situation but also affect one’s future behavior. To elucidate the potential causal influence of life satisfaction on fertility outcomes, various estimation methodologies including ordinary least square and instrumental variables analyses were utilized on a well-known panel dataset (the British Household Panel Survey). The findings in general were as expected across main analyses and robustness checks. Average level of and amount of drop in life satisfaction around the period of first child birth were positively and negatively associated with probability of having a second child, respectively. Based on the results obtained, implications and limitations were discussed.
Thesis(Master) --KDI School:Master of Development Policy,2016